THE CONCEPT OF SELF-DEFENSE IN AMERICAN AND POLISH LEGAL SYSTEMS – A COMPARATIVE ANALYSIS - Ginszt, Katarzyna; Ginszt, Jakub (Review of European and Comparative Law, 2017)
The article is devoted to the issue of self-defense in Polish and American law . Currently, there are attempts to widen the scope of necessary self-protection in Polish legislation and to implement provisions which allow for using greater degree of force by a person attacked at home . The justification of the draft refers to the American law which is more developed in the context of the defense of habitation . Thus, the article provides an analysis of existing legal solutions in American criminal law concerning e .g . the legal definition of self-defense, the use of deadly force, the duty to retreat, the castle doctrine and the provisions which expand this doctrine in comparison with the parallel legal solutions existing in Poland .